2018
DOI: 10.1096/fj.201700717rr
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic programming at the Mogat1 locus may link neonatal overnutrition with long‐term hepatic steatosis and insulin resistance

Abstract: Postnatal overfeeding increases the risk of chronic diseases later in life, including obesity, insulin resistance, hepatic steatosis, and type 2 diabetes. Epigenetic mechanisms might underlie the long-lasting effects associated with early nutrition. Here we aimed to explore the molecular pathways involved in early development of insulin resistance and hepatic steatosis, and we examined the potential contribution of DNA methylation and histone modifications to long-term programming of metabolic disease. We used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 52 publications
3
20
0
Order By: Relevance
“…24 However, inflammation or insulin resistance is also factors that can cause cardiac dysfunctions. 25,26 Thus, we have observed cardiovascular impairments in adult animals that have been subjected to FR during puberty, seen in the cardiac remodeling and the changes in expression of molecular mediators responsible for controlling cardiac homeostasis. We can surmise that FR during puberty is a cardiometabolic programming factor, particularly when we consider the NLFR group, which has shown that the impairments observed are independent from the presence of previous metabolic programming by EO.…”
Section: Discussionmentioning
confidence: 99%
“…24 However, inflammation or insulin resistance is also factors that can cause cardiac dysfunctions. 25,26 Thus, we have observed cardiovascular impairments in adult animals that have been subjected to FR during puberty, seen in the cardiac remodeling and the changes in expression of molecular mediators responsible for controlling cardiac homeostasis. We can surmise that FR during puberty is a cardiometabolic programming factor, particularly when we consider the NLFR group, which has shown that the impairments observed are independent from the presence of previous metabolic programming by EO.…”
Section: Discussionmentioning
confidence: 99%
“…MOGAT1 gene is involved in the glycerolipid metabolism (ko00561), and codes the MGAT (monoacylglycerol acyltransferases) enzyme, which is active in human liver and its activity can represent a viable target for pharmacologic intervention to treat nonalcoholic fatty liver disease [38]. A study reported that up-regulation of MOGAT1 gene can mediate hepatic steatosis by increasing intracellular diacylglycerol content [39]. In this study, g.111599360A > G in 5′ flanking region of MOGAT1 was predicted to create the TFBSs for PAX6 with the allele A and TEAD4 with the allele G. PAX6 can respectively down-regulate Sox3 and up-regulate Lhx9 in the Pax6-mutant cortex to exert its effects at the molecular level during murine forebrain neurogenesis [40].…”
Section: Discussionmentioning
confidence: 99%
“…This difference may be attributed to the type and timing of early-life exposure. In a model of neonatal overfeeding in mice, monoacylglycerol O-acyltransferase ( Mogat1 ) was identified as a potential early mediator of hepatic IR and steatosis, with a 3-fold upregulation accompanied by a 50% reduction in the enrichment of the repressive histone mark H3K27me3 ( 157 ). The Mogat1 enzyme catalyses the conversion of monoacylglycerol to diacylglycerol (DAG), a molecule which may directly interfere with the insulin signalling cascade ( 158 ).…”
Section: Altering the Liver Epigenomementioning
confidence: 99%